Primatology in zoos: Studying behavior, cognition, and welfare. Issue 10 (22nd April 2022) - Hopper, Lydia M.
Abstract: Primatological research in zoos is increasing globally. Such research allows scientists to study primate biology, behavior, and cognition while helping to advance the welfare of captive primates. Moreover, zoos welcome millions of visitors annually, which creates unique opportunities for public engagement with this research. Reflecting the importance of zoos in the field of primatology, the articles in this special issue showcase the range of primatological research currently being conducted in zoos around the world. With this special issue, I have chosen to focus on research examining primate behavior and cognition, addressing both basic and applied questions. The articles included in this special issue also highlight the array of technologies and methods being used to study zoo‐housed primates. While zoos house a variety of primate species, potentially enabling the testing of under‐studied species or widescale comparative research, great apes are disproportionately represented in current zoo‐based research. Thus, while an interest in conducting research with primates in zoos continues to grow, there are still opportunities to increase the breadth and diversity of this study. Highlights: Primatological research in zoos is increasing globally. Such research allows scientists to study primate biology, behavior, and cognition. This research helps to advance the welfare of captive primates. While zoos house many primate species, apes are disproportionately represented in current zoo research. Abstract :